2017
DOI: 10.1016/j.ebiom.2017.03.046
|View full text |Cite
|
Sign up to set email alerts
|

Biological Age Predictors

Abstract: The search for reliable indicators of biological age, rather than chronological age, has been ongoing for over three decades, and until recently, largely without success. Advances in the fields of molecular biology have increased the variety of potential candidate biomarkers that may be considered as biological age predictors. In this review, we summarize current state-of-the-art findings considering six potential types of biological age predictors: epigenetic clocks, telomere length, transcriptomic predictors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
747
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 870 publications
(759 citation statements)
references
References 78 publications
8
747
0
4
Order By: Relevance
“…In parallel with the epigenetic clock (Horvath, 2013;Jones, Goodman, & Kobor, 2015;Jylhävä, Pedersen, & Hägg, 2017), EEG-estimated brain maturation might become a tool that address questions concerning developmental trajectories. In addition, we have shown that the prediction error is not random noise, but moderately stable over a period of about 1.5 years, and to a large extent influenced by the genetic background of the subject.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel with the epigenetic clock (Horvath, 2013;Jones, Goodman, & Kobor, 2015;Jylhävä, Pedersen, & Hägg, 2017), EEG-estimated brain maturation might become a tool that address questions concerning developmental trajectories. In addition, we have shown that the prediction error is not random noise, but moderately stable over a period of about 1.5 years, and to a large extent influenced by the genetic background of the subject.…”
Section: Discussionmentioning
confidence: 99%
“…Biological aging denotes the heterogeneity of different biomarkers, genomic predictors, epigenetic clocks and biological processes in individuals. While biological aging is seen in many chronic diseases, we have little understanding on how it could be utilized as a true biomarker …”
Section: Discussionmentioning
confidence: 99%
“…Based on information in the section above, developing a proxy measure of biological aging for humans still requires work but is a very dynamic and promising area of investigation with strong potential for translation. Some of the measures described-namely mitochondrial function, DNA methylation, and, to a lesser extent, cellular senescence and autophagy-are ready to be implemented based on several epidemiological studies, although refinements are always possible Choi et al, 2016;Cohen, Morissette-Thomas, Ferrucci, & Fried, 2016;Jylhävä, Pedersen, & Hägg, 2017;Jylhävä et al, 2014;Kananen et al, 2016;Kent & Fitzgerald, 2016;Kim & Jazwinski, 2015;Levine et al, 2018;Li et al, 2018;Marioni et al, 2019;Marttila et al, 2015;Putin et al, 2017;Sillanpää et al, 2018). Measures of telomere length are hampered by noise and wide longitudinal variations that cannot be explained by health events and at this stage are not useful for measuring biological age (Arai et al, 2015;Jodczyk, Fergusson, Horwood, Pearson, & Kennedy, 2014;Tomaska & Nosek, 2009).…”
Section: Connec Ting the B I Ology Of Ag Ing With Ag E-a Sso Ciatedmentioning
confidence: 99%